2020
DOI: 10.1002/joc.6820
|View full text |Cite
|
Sign up to set email alerts
|

Changes of extreme climate events and related risk exposures in Huang‐Huai‐Hai river basin under 1.5–2°C global warming targets based on high resolution combined dynamical and statistical downscaling dataset

Abstract: Extreme climate events and related risk exposures in Huang‐Huai‐Hai (HHH) river basin were projected under global warming of 1.5–2°C using the high‐resolution combined dynamical and statistical downscaling dataset. Firstly, evaluation indicated that the dataset can well reproduce the spatial distribution of all temperature extremes and most of the precipitation extremes, providing a reliable ability for future projections. Then, projections showed that the hot events were projected to increase, while the cold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Based on the framework of the East Asia domain from CORDEX phase II (Giorgi et al, 2009), the simulation domain here encompassed the whole of continental China and adjacent areas (Figure 1). Previous studies have reported detailed information about the model parameterization schemes, evaluation results, and applied studies (Gao et al, 2017(Gao et al, , 2018Han et al, 2019;Shi et al, 2018;Wu et al, 2020Wu et al, , 2021. To examine the regional changes of solar energy, we divided China into eight subregions, as per China's National Assessment Report on Climate Change (National Report Committee, 2011;Zhou et al, 2015) (Figure 1): NEC (northeast China), NC (north China), EC (east China), CC (central China), SC (south China), SWC1 (Tibetan Plateau), SWC2 (southwest China), and NWC (northwest China).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the framework of the East Asia domain from CORDEX phase II (Giorgi et al, 2009), the simulation domain here encompassed the whole of continental China and adjacent areas (Figure 1). Previous studies have reported detailed information about the model parameterization schemes, evaluation results, and applied studies (Gao et al, 2017(Gao et al, , 2018Han et al, 2019;Shi et al, 2018;Wu et al, 2020Wu et al, , 2021. To examine the regional changes of solar energy, we divided China into eight subregions, as per China's National Assessment Report on Climate Change (National Report Committee, 2011;Zhou et al, 2015) (Figure 1): NEC (northeast China), NC (north China), EC (east China), CC (central China), SC (south China), SWC1 (Tibetan Plateau), SWC2 (southwest China), and NWC (northwest China).…”
Section: Methodsmentioning
confidence: 99%
“…Solar radiation (SR), surface temperature (TM), surface wind speed (SW) results were obtained from the above sets of dynamical downscaling outputs. Their ensemble mean (hereafter referred to as ENS) was calculated using the equal‐weighted average method (Han et al., 2019; Wu et al., 2021). To comprehensively validate the model performance, two types of reference data were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the RCMs also exhibit systematic biases that are likely dependent on the GCM boundary and model internal dynamics (Giorgi, 2007; Teutschbein & Seibert, 2012). The errors in RCMs, despite their high spatial resolution, lead to large uncertainty in projection studies and limit their application in regional climate change impacts studies (Cubasch et al., 2001; Kattenberg, 1996; Pastén‐Zapata et al., 2020; Stocker et al., 2013; Van der Linden & Mitchell, 2009; Wu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To accurately grasp China's future population growth tendency, the projections of NUIST (Nanjing University of Information Science and Technology) and THU (Tsinghua University) were created recently by Huang et al 21 and Chen et al 22 , respectively. These spatially explicit population datasets have been widely used to explore the influence of future population levels on global climate change 23 – 26 , extreme weather disaster events 27 29 , land-use change 24 , and ecosystem service change 30 . Although they have been applied in many research fields, we know little about their projection accuracy and poorly understand the factors that affect their projection accuracy.…”
Section: Introductionmentioning
confidence: 99%